2005
DOI: 10.4103/0019-5359.16651
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anticardiolipin antibodies and antiphosphatidylserine antibodies in women with recurrent abortion

Abstract: BACKGROUND: Antiphospholipid syndrome (APS) is a major reproductive complication in women, which is characterized by recurrent fetal loss, thrombosis, and thrombocytopenia in association with anticardiolipin antibodies (aCL). AIMS: To analyze the prevalence of aCL and antiphosphatidylserine antibodies (aPS) in relation to pregnancy failures in women with the history of recurrent spontaneous abortion. SETTINGS AND DESIGN: A sequential study of 155 patients, who had three or more recurrent spontaneous abortions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“… 10 The presence of aCL and LA in various Indian studies has been reported to be 5.3 to 21% and 6.25%, respectively. 3 , 4 , 12 Some authors have described concordance rates for positive LA and aCL results ranging from 60 to 90%, 13 but in this study none of the ten positive samples showed such concordance. Therefore, we are of the opinion that all samples must be tested for both aCL and LA.…”
Section: Discussioncontrasting
confidence: 54%
“… 10 The presence of aCL and LA in various Indian studies has been reported to be 5.3 to 21% and 6.25%, respectively. 3 , 4 , 12 Some authors have described concordance rates for positive LA and aCL results ranging from 60 to 90%, 13 but in this study none of the ten positive samples showed such concordance. Therefore, we are of the opinion that all samples must be tested for both aCL and LA.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly in 2005 Archunan and his colleagues reported 40% positive anticardiolipin antibodies cases in women with history of recurrent fetal losses. (Archunan, 2005). In another study done by Creagh et al (1999), sample size of 35 women with history of recurrent fetal losses showed 17.1% positive anticardiolipin antibodies (Creagh, 1999).…”
Section: Discussionmentioning
confidence: 94%